Responsibilitas Kinerja Kantor Pelayanan Perbendaharaan Negara Surabaya II Dalam Pencairan Dana - Manik, Betseba Putricia; Widiyarta, Agus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Responsibility is a measure of how well government administrators exercise their authority in providing and delivering services according to established procedures and regulations. The National Treasury Service Office of Surabaya II can be considered responsible if it performs its duties to the best of its ability and utilizes all available resources effectively and efficiently. This study aims to analyze and describe the responsibility of the service performance of the National Treasury Service Office of Surabaya II in the disbursement of State Budget funds. The research employs a qualitative method with data collection techniques including interviews, observations, and documentation. The results of the study indicate that: 1) The understanding of responsibility in fund disbursement services is good, as employees understand their responsibilities and work units find it easy to submit fund disbursement requests. 2) The delegation of authority corresponding to responsibility in fund disbursement services is excellent, as the authority granted is equivalent to the responsibility assigned. 3) Performance evaluation in fund disbursement services is good, as regular evaluations are conducted with the aim of making improvements in the future. 4) Accurate, fair, and timely actions in providing fund disbursement services are not yet optimal due to the instability of processing times experienced by work units. 5) The commitment of leadership in service delivery is strong, as leaders are committed to entrusting duties and responsibilities to their subordinates.